To sign or not to sign? On the response of prices to financial and uncertainty shocks - Philipp Meinen; Oke Röhe (Deutsche Bundesbank, 2018)
Based on SVAR models identified by sign restrictions, we estimate the macroeconomic effects of financial and uncertainty shocks in the euro area and the US, paying particular attention to their effects on prices. While our results confirm that such disturbances are important drivers of output fluctuations in both economies, we find the shock responses of consumer prices to be ambiguous. Moreover, restricting prices to co-moving with output can considerably attenuate the measured impact of financial and uncertainty shocks on real activity.
Keywords: C11; C32; E32; E44; 330; Financial Shocks; Uncertainty Shocks; Sign Restrictions; Euro Area; United States